Inbound tourism and the marketization of China's institutions: Analysis of regional panel data. Issue 4 (7th November 2016) - Ma, Jing; Liu, Shuo
Abstract : Purpose: The purpose of this paper is to examine whether the institutions play a role in tourism development and international recognition, specifically the influence of marketization on the international tourists' inbound arrivals in different Chinese provinces. Design/methodology/approach: This paper constructs a demand model of tourism and empirically analyzes the relationship between marketization and inbound tourism demand with the panel data of the provinces of China and NERI Index of Marketization. Findings: Marketization does have an influence on inbound tourism demand of China. Specially, the relationship between government and market, the development of product market, the market intermediary organizations and the legal system environment can increase the demand of the foreign tourists to visit China, although the magnitudes are different. Practical implications: This paper argues that the qualities of marketization intuitions are important in increasing inbound tourism, given that it can bring better tourism experience and improve the international recognition. Strengthening the legislation and protecting the legitimate rights and interests of consumers can attract more international travelers to China. Market distribution of competitive economic resources, reducing political intervention into corporate activities and relieving tax burdens of enterprises can improve the competitiveness and the service qualities of Chinese domestic tourism firms. Originality/value: This paper leads the discussions of institutions and tourism. It combines the consumer theory and uses static and dynamic panel data models to analyze the influencing factors of Chinese tourism. It argues that Chinese inbound tourism shall develop with the systemic marketization progress in China.